2022
DOI: 10.1038/s41467-022-30836-0
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID burden and risk factors in 10 UK longitudinal studies and electronic health records

Abstract: The frequency of, and risk factors for, long COVID are unclear among community-based individuals with a history of COVID-19. To elucidate the burden and possible causes of long COVID in the community, we coordinated analyses of survey data from 6907 individuals with self-reported COVID-19 from 10 UK longitudinal study (LS) samples and 1.1 million individuals with COVID-19 diagnostic codes in electronic healthcare records (EHR) collected by spring 2021. Proportions of presumed COVID-19 cases in LS reporting any… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
300
16
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(361 citation statements)
references
References 39 publications
37
300
16
8
Order By: Relevance
“…The socio-demographic data showed that most participants were under 40 years old, representing the general population of Saudi Arabia [ 27 ]. This study revealed that elderly age (>65 years old) predicts the probability of having a possible risk factor for post-COVID-19 conditions ( Table 2 ), which was also in line with previous studies that reported that older age is a risk for developing long-COVID-19 symptoms [ 16 ]. However, it is well known that aging is associated with dysregulated immune responses, which may increase susceptibility or persistence to viral-related infection [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The socio-demographic data showed that most participants were under 40 years old, representing the general population of Saudi Arabia [ 27 ]. This study revealed that elderly age (>65 years old) predicts the probability of having a possible risk factor for post-COVID-19 conditions ( Table 2 ), which was also in line with previous studies that reported that older age is a risk for developing long-COVID-19 symptoms [ 16 ]. However, it is well known that aging is associated with dysregulated immune responses, which may increase susceptibility or persistence to viral-related infection [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, studies on the community’s post-COVID-19 conditions are limited, especially in the Middle East. One previous study in the UK that coordinated analysis of survey data from 6907 individuals and 1.1 million individuals with COVID-19 diagnostic codes in electronic healthcare records data concluded that the proportion of long COVID-19 ranged from 7.8% to 17% [ 16 ]. In another prospective cohort study, in Russia, the authors included around 3358 adults and children with confirmed COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery from post-COVID conditions can be slow, and symptoms may affect the individual’s function and impede return to work (RTW). It has been estimated that 1.2 % - 4.8% of COVID-19 patients will develop post-COVID conditions with debilitating symptoms [ 3 ].…”
mentioning
confidence: 99%
“…Together, OSC28 and PCS84 are known colloquially as 'Long COVID'. The strongest predictors of PCS84 are age (with those aged 35-69 years having highest risk), female sex, and greater severity of acute infection 7,8 Whilst vaccination against SARS-CoV-2 reduces the risk and duration of PCS84 [9][10][11] , prolonged post-infection symptomatology remains common. The United Kingdom Office for National Statistics report 2 million affected individuals in the United Kingdom by 01 May 2022, and 71% of individuals report that this affects normal daily activities…”
mentioning
confidence: 99%